Extensive Listening Challenges through the Lens of the East Indonesian EFL Learners - Yosefina Rosdiana Su; Rudi Hartono; Issy Yuliasri; Widhiyanto Widhiyanto (Universitas Negeri Semarang, 2023)
The benefits of extensive listening have been documented in several studies, particularly in English as a Foreign Language (EFL) listening. These studies constructed the theoretical and pedagogical frameworks for its implementation, including the typical materials students can utilize to organize extensive listening practices. In light of this, this paper presents a brief overview of the listening materials used by the students in this setting and the challenges they faced in utilizing them for extensive listening practices. This qualitative study was designed as a survey involving 79 students from a private university in East Nusa Tenggara, Indonesia. In collecting the data, the researchers administered an unstructured questionnaire combining close-ended and open-ended questions providing chances for the respondents to answer the questions in their own words. The result of this study confirmed that extensive listening is challenging to practice. In this case, students need knowledge about the pedagogy of extensive listening practices results in inappropriate material selections. This study recommends teachers' involvement in assisting the material selection that meets the student's pace to help students achieve more definite outcomes of the extensive listening practices.